Stem Education in Science Learning: Systematic Literature Review - Rudi Pranata; Syahril; Ruth Rize Paas Megahati S. (Postgraduate, University of Mataram, 2023)
As one of the efforts to produce Sumber Human Resources (HR) who have century competence 21st, a learning design is needed which integrates skills or 21st century skills. By including students are involved in remembering, understanding, apply, analyze, evaluate as well create both in scientific theory and at the time their daily life. A review is conducted on the state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guideline. We review literature from several publications and analyze STEM approach is a very appropriate approach to use in 21st century learning. After applying STEM approach, students are expected to be able mastering scientific and technological literacy. In learning there is a process of interaction between educators and students and learning resources in a learning environment to achieve learning goals. Learning is done using learning strategies in facilitating the teaching and learning process. So that the process can be carried out properly and conveyed correctly, STEM learning is carried out which can integrate knowledge, skills and values of science, technology, engineering, and mathematics to be able to solve a problem related to learning in the context of everyday life. Â